PENDIDIKAN KESEHATAN TENTANG PENGOBATAN PADA PASIEN TUBERCULOSIS PARU DI RUMAH SAKIT TK II PUTRI HIJAU MEDAN TAHUN 2021 - enny fitriani; Doni Hariansyah; Deni Susyanti; Muchti Yuda Pratama (Journal of Indah Science and Clinic, 2021)
Background: Tuberculosis is direct infectious disease caused by mycobacterium tuberculosis which transmitted through the air (droplet nuclei) when a patient with tuberculosis cough and the saliva droplets that containing the bacteria were inhaled by another person while breathing. The period of treatments for pulmonary tuberculosis required complete adherence. Irregular treatment is caused by the habit that the patient already felt healthy and does not spend the drugs completely and also the side effects of the drugs that make the patient unable to stand it then stop taking the drugs.There were some reasons that lead to the resistance pulmonary tuberculosis bacteria to OAT or MDR-TB. The knowledge management for uneducated patients is needed by providing health education about the treatment of tuberculosis.Methods: The study used descriptive study by involving nursing process which include of assessment, diagnosis,intervention, implementation and evaluation on two patients with pulmonary tuberculosis at TK II Putri Hijau Hospital Medan. Results: It was obtained that the lack of knowledge problem could be resolved in patient I while in patient II the problem was partially resolved.